LEARNING STYLES AND ACHIEVEMENT IN SOCIAL SCIENCES AND NATURAL SCIENCES ON SECONDARY SCHOOL'STUDENTS - Esteban, Manuel; Ruiz, Cecilia; Cerezo Ramírez, Fuensanta (Anales de Psicología / Annals of Psychology)
This survey has a double objective: firstly, its aim is an exploratory approach to confirm pertinence of a relation among learning styles and academic success, and secondly, to know if we can talk about learning styles associated to determined academic disciplines, in our case to social and natural sciences.Sample is made up of 337 students in their second cycle of Secondary Education in the region of Murcia. Most of them are 15 to 18 years old and belong to the following specialities: Sciences, Technology, Humanities and Administrative. They were given the Shmeck and col. ILP-R questionnaire in its Spanish version, validated by Esteban, Ruiz and Cerezo (1996a).According to data from this research we can state that there are significant differences among learning styles in individuals with a high and a low performance generally speaking, and according to specialities. The variable "efficacy" (Cognitive organization, Critical thinking, and Fact retention), together with support variables as motivation are in most cases the ones setting significant differences among good students in social sciences and natural sciences.